Latex composition and dip-molded product

The latex composition, featuring specific conjugated diene polymers, addresses the challenge of achieving high tear strength and short aging times in dip-molded products, enhancing their mechanical properties and safety by using synthetic polymers instead of natural rubber.

JP7604942B2Active Publication Date: 2024-12-24ZEON CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021029821
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-26
Publication Date
2024-12-24
Estimated Expiration
2041-02-26

AI Technical Summary

Technical Problem

Existing latex compositions for dip-molded products, such as gloves and balloons, face challenges in achieving high tear strength while maintaining short aging times and avoiding allergic reactions due to the use of natural rubber latex, which contains proteins causing immediate allergies.

Method used

A latex composition comprising a water-insoluble conjugated diene polymer with an absorbance of 0.3 or more at pH=8 and a latex of an alkali-soluble conjugated diene polymer with an absorbance of less than 0.3 at pH=8, obtained through emulsion polymerization, is used to create dip-molded products with high tear strength and reduced aging times.

Benefits of technology

The latex composition enables dip-molded products to achieve high tear strength at relatively low temperatures and in a short aging time, improving productivity and reducing the risk of allergic reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604942000001
    Figure 0007604942000001
Patent Text Reader

Abstract

To provide a latex composition capable of imparting a film forming material such as a dip molding having high tearing strength at a relatively low temperature and within a short aging time.SOLUTION: A latex composition containing a latex of a water-insoluble conjugated diene polymer (A) having an absorbance of 0.3 or more at pH=8 and a solid content concentration of 3 wt.%, and a latex of pH=8 and an absorbance of smaller than 0.3 at a solid content concentration of 3 wt.%, in which the latex of the alkali-soluble conjugated diene polymer (B) is obtained by emulsifying polymerization of a monomer mixture containing a conjugated diene monomer and a water soluble monomer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a latex composition which can provide a film-formed article, such as a dip-formed article, having high tear strength at a relatively low temperature and in a short maturation time. [Background technology]

[0002] It has been known that latex compositions containing natural rubber latex are dip molded to obtain dip molded articles such as nipples, balloons, gloves, balloons, and sacks that are used in contact with the human body. However, natural rubber latex contains proteins that cause immediate-type allergy (Type I) symptoms in the human body, and therefore may be problematic as a dip molded article that comes into direct contact with the mucous membranes or organs of the body. Therefore, the use of synthetic rubber latex instead of natural rubber latex has been investigated.

[0003] For example, Patent Document 1 discloses a latex composition for dip molding, which contains a synthetic polyisoprene latex having a weight-average molecular weight of 10,000 to 5,000,000, a polycarboxylic acid and / or a salt of a polycarboxylic acid, a sulfur-based vulcanizing agent, and a vulcanization accelerator. In the technology of the latex composition for dip molding as in Patent Document 1, from the viewpoint of stably maintaining high mechanical strength of the obtained film molded body such as a dip molded body, it is common to add a crosslinking agent such as a sulfur-based vulcanizing agent and then perform aging (pre-vulcanization). According to the technology of Patent Document 1, sufficient mechanical strength is obtained even when the aging time is relatively short at 24 hours, but from the viewpoint of improving productivity, further shortening of the aging time has been desired. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2015 / 046391 Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a latex composition which can provide a film-formed article, such as a dip-formed article having high tear strength, at a relatively low temperature and in a short maturation time. [Means for solving the problem]

[0006] As a result of intensive research to solve the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by a latex composition obtained by blending a latex of an alkali-soluble conjugated diene polymer (B) which is obtained by emulsion polymerization of a monomer mixture containing a conjugated diene monomer and a water-soluble monomer, with a latex of a water-insoluble conjugated diene polymer (A) having an absorbance at 500 nm of 0.3 or more at a pH of 8 and a solid content of 3% by weight, and which has an absorbance of less than 0.3 at a pH of 8 and a solid content of 3% by weight. Based on this finding, the present inventors have completed the present invention.

[0007] That is, according to the present invention, a latex of a water-insoluble conjugated diene polymer (A) having an absorbance of 0.3 or more at pH=8 and a solid content concentration of 3% by weight, and a latex of an alkali-soluble conjugated diene polymer (B) having an absorbance of less than 0.3 at pH=8 and a solid content concentration of 3% by weight, The latex of the alkali-soluble conjugated diene polymer (B) is obtained by emulsion polymerization of a monomer mixture containing a conjugated diene monomer and a water-soluble monomer, thereby providing a latex composition.

[0008] In the latex composition of the present invention, the latex of the alkali-soluble conjugated diene polymer (B) preferably has a volume average particle size of 60 to 200 nm at pH 6 or less. In the latex composition of the present invention, the content of the water-soluble monomer units in the alkali-soluble conjugated diene polymer (B) is preferably 20 to 80% by weight in 100% by weight of all monomer units. In the latex composition of the present invention, the alkali-soluble conjugated diene polymer (B) is preferably obtained by emulsion polymerization of a monomer mixture containing isoprene and a carboxyl group-containing monomer. In the latex composition of the present invention, the carboxyl group-containing monomer is preferably methacrylic acid.

[0009] According to the present invention, there is also provided a dip-molded article obtained by dip molding the above-mentioned latex composition. Effect of the Invention

[0010] According to the present invention, there can be provided a latex composition which can give a film-formed article, such as a dip-formed article, having high tear strength at a relatively low temperature and in a short maturing time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] <Latex composition> The latex composition of the present invention comprises a latex of a water-insoluble conjugated diene polymer (A) having an absorbance of 0.3 or more at pH=8 and a solid content concentration of 3% by weight; and a latex of an alkali-soluble conjugated diene polymer (B) having an absorbance of less than 0.3 at pH=8 and a solid content concentration of 3% by weight, The latex of the alkali-soluble conjugated diene polymer (B) is obtained by emulsion polymerization of a monomer mixture containing a conjugated diene monomer and a water-soluble monomer.

[0012] The latex of the water-insoluble conjugated diene polymer (A) having an absorbance of 0.3 or more at a pH of 8 and a solid content of 3% by weight (hereinafter, appropriately referred to as "latex of water-insoluble conjugated diene polymer (A)") used in the present invention is a latex of the water-insoluble conjugated diene polymer (A), and the absorbance of the latex at a pH of 8 and a solid content of 3% by weight is 0.3 or more, preferably 1.0 or more, more preferably 1.6 or more, and it is sufficient that the latex is insoluble in water or is poorly water-soluble. It is desirable that the absorbance is 0.3 or more, preferably 1.0 or more, more preferably 1.6 or more, not only at pH 8 but also in a wide pH range of pH 2 to 14, and that the latex is insoluble in water or is poorly water-soluble in water in a wide pH range.

[0013] The absorbance of the latex of the water-insoluble conjugated diene polymer (A) at pH=8 and solid content concentration of 3% by weight can be measured as absorbance at 500 nm with a spectrophotometer at a temperature of 25° C. in a state where pH is 8 and solid content is 3% by weight by adding a pH adjuster such as sulfuric acid, nitric acid, sodium hydroxide, or potassium hydroxide to the latex of the water-insoluble conjugated diene polymer (A) and water. Since the latex of the water-insoluble conjugated diene polymer (A) contains particles of the water-insoluble conjugated diene polymer (A) dispersed in water as a medium at pH=8, the latex shows an absorbance value of 0.3 or more at pH=8 and solid content concentration of 3% by weight. In addition, the latex of the water-insoluble conjugated diene polymer (A) is preferably one in which particles of the water-insoluble conjugated diene polymer (A) are dispersed in water as a medium not only at pH=8 but also in a wide pH range of pH=2 to 14, and thus preferably has an absorbance of 0.3 or more at a solids concentration of 3 wt% in a wide pH range of pH=2 to 14.

[0014] The volume average particle diameter of the particles of the water-insoluble conjugated diene polymer (A) constituting the latex of the water-insoluble conjugated diene polymer (A) is preferably 0.1 to 10 μm, more preferably 0.5 to 3 μm, and even more preferably 0.5 to 2.0 μm, and the latex of the water-insoluble conjugated diene polymer (A) is preferably one that is not water-soluble or is poorly water-soluble at pH=8, and preferably not only at pH=8 but also in a wide pH range of pH=2 to 14, and has the above-mentioned volume average particle diameter at pH=8 and further in such a wide pH range. The volume average particle diameter can be measured using a laser diffraction particle size distribution analyzer.

[0015] Such a latex of a water-insoluble conjugated diene polymer (A) is not particularly limited, but examples thereof include a synthetic polyisoprene latex, a styrene-isoprene-styrene block copolymer (SIS) latex, a natural rubber latex from which proteins have been removed (deproteinized natural rubber), a nitrile group-containing conjugated diene copolymer latex, etc. Among these, a polymer latex containing an isoprene unit, such as a synthetic polyisoprene latex, a SIS latex, or a deproteinized natural rubber latex, is preferred, and a synthetic polyisoprene latex is particularly preferred.

[0016] When synthetic polyisoprene latex is used as the latex of the water-insoluble conjugated diene polymer (A), the synthetic polyisoprene contained in the synthetic polyisoprene latex may be a homopolymer of isoprene or may be a copolymer of isoprene and other ethylenically unsaturated monomers copolymerizable therewith. The content of isoprene units in the synthetic polyisoprene is preferably 70% by weight or more, more preferably 90% by weight or more, even more preferably 95% by weight or more, and particularly preferably 100% by weight (homopolymer of isoprene) based on the total monomer units, since it is easy to obtain a membrane molded product such as a dip molded product that is flexible and has excellent tensile strength.

[0017] Examples of other ethylenically unsaturated monomers copolymerizable with isoprene include conjugated diene monomers other than isoprene, such as butadiene, chloroprene, and 1,3-pentadiene; ethylenically unsaturated nitrile monomers, such as acrylonitrile, methacrylonitrile, fumaronitrile, and α-chloroacrylonitrile; vinyl aromatic monomers, such as styrene and alkylstyrene; ethylenically unsaturated carboxylate monomers, such as methyl (meth)acrylate (meaning "methyl acrylate and / or methyl methacrylate", hereinafter the same applies to ethyl (meth)acrylate, etc.), ethyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; and the like. These other ethylenically unsaturated monomers copolymerizable with isoprene may be used alone or in combination.

[0018] Synthetic polyisoprene can be obtained by a conventionally known method, for example, by solution polymerization of isoprene and other copolymerizable ethylenically unsaturated monomers used as necessary in an inert polymerization solvent using a Ziegler-based polymerization catalyst consisting of trialkylaluminum-titanium tetrachloride or an alkyl lithium polymerization catalyst such as n-butyl lithium or sec-butyl lithium. The polymer solution of synthetic polyisoprene obtained by solution polymerization may be used as it is for the production of synthetic polyisoprene latex, but solid synthetic polyisoprene can also be taken out of the polymer solution and then dissolved in an organic solvent for use in the production of synthetic polyisoprene latex. When the synthetic polyisoprene polymer solution is obtained by the above-mentioned method, impurities such as the residue of the polymerization catalyst remaining in the polymer solution may be removed. In addition, an antioxidant described later may be added to the solution during or after the polymerization. In addition, commercially available solid synthetic polyisoprene may be used.

[0019] There are four types of isoprene units in synthetic polyisoprene, depending on the bonding state of isoprene: cis bond unit, trans bond unit, 1,2-vinyl bond unit, and 3,4-vinyl bond unit. From the viewpoint of improving the tensile strength of the obtained film molded article such as a dip molded article, the content of cis bond units in the isoprene units contained in the synthetic polyisoprene is preferably 70% by weight or more, more preferably 90% by weight or more, and even more preferably 95% by weight or more, based on the total isoprene units.

[0020] The weight-average molecular weight of the synthetic polyisoprene is preferably 10,000 to 5,000,000, more preferably 500,000 to 5,000,000, and even more preferably 800,000 to 3,000,000, as calculated based on standard polystyrene by gel permeation chromatography analysis. By setting the weight-average molecular weight of the synthetic polyisoprene within the above range, the tensile strength and tensile elongation of the obtained film molded product such as a dip molded product are further improved, and the synthetic polyisoprene latex tends to be easily produced.

[0021] In addition, the polymer Mooney viscosity (ML 1+4 , 100° C.) is preferably 50 to 80, more preferably 60 to 80, and further preferably 70 to 80.

[0022] Methods for obtaining synthetic polyisoprene latex include, for example, (1) a method in which a solution or fine suspension of synthetic polyisoprene dissolved or finely dispersed in an organic solvent is emulsified in water in the presence of an emulsifier, and the organic solvent is removed as necessary to produce a synthetic polyisoprene latex, and (2) a method in which isoprene alone or a mixture of isoprene and an ethylenically unsaturated monomer copolymerizable therewith is emulsion polymerized or suspension polymerized in the presence of an emulsifier to directly produce a synthetic polyisoprene latex. Among these, the above-mentioned production method (1) is preferred in that it can use synthetic polyisoprene having a high ratio of cis-bond units in the isoprene units and can easily produce a film molded product such as a dip molded product having excellent mechanical properties such as tensile strength.

[0023] Examples of the organic solvent used in the above production method (1) include aromatic hydrocarbon solvents such as benzene, toluene, xylene, etc.; alicyclic hydrocarbon solvents such as cyclopentane, cyclopentene, cyclohexane, cyclohexene, etc.; aliphatic hydrocarbon solvents such as pentane, hexane, heptane, etc.; halogenated hydrocarbon solvents such as methylene chloride, chloroform, ethylene dichloride, etc. Among these, alicyclic hydrocarbon solvents and aliphatic hydrocarbon solvents are preferred, pentane, cyclohexane, and n-hexane are more preferred, and n-hexane is particularly preferred.

[0024] The amount of the organic solvent used is preferably 2,000 parts by weight or less, more preferably 20 to 1,500 parts by weight, and even more preferably 500 to 1,500 parts by weight, based on 100 parts by weight of the synthetic polyisoprene.

[0025] As the emulsifier used in the above production method (1), it is preferable to use an ionic emulsifier, and among these, it is more preferable to use an anionic emulsifier. Examples of the anionic emulsifier include fatty acid salts such as sodium laurate, potassium myristate, sodium palmitate, potassium oleate, sodium linolenate, sodium rosinate, and potassium rosinate; alkylbenzenesulfonates such as sodium dodecylbenzenesulfonate, potassium dodecylbenzenesulfonate, sodium decylbenzenesulfonate, potassium decylbenzenesulfonate, sodium cetylbenzenesulfonate, and potassium cetylbenzenesulfonate; alkylsulfosuccinates such as sodium di(2-ethylhexyl)sulfosuccinate, potassium di(2-ethylhexyl)sulfosuccinate, and sodium dioctylsulfosuccinate; alkyl sulfates such as sodium lauryl sulfate and potassium lauryl sulfate; polyoxyethylene alkyl ether sulfates such as sodium polyoxyethylene lauryl ether sulfate and potassium polyoxyethylene lauryl ether sulfate; and monoalkyl phosphates such as sodium lauryl phosphate and potassium lauryl phosphate.

[0026] Among these anionic emulsifiers, fatty acid salts, alkylbenzenesulfonates, alkylsulfosuccinates, alkyl sulfates and polyoxyethylene alkyl ether sulfates are preferred, with fatty acid salts and alkylbenzenesulfonates being particularly preferred.

[0027] In addition, it is preferable to use at least one selected from the group consisting of alkylbenzenesulfonate, alkylsulfosuccinate, alkylsulfuric acid ester salt, and polyoxyethylene alkyl ether sulfate salt in combination with a fatty acid salt, since it is possible to more efficiently remove a trace amount of polymerization catalyst (particularly aluminum and titanium) derived from synthetic polyisoprene and suppress the generation of coagulation during the production of a latex composition, and it is particularly preferable to use an alkylbenzenesulfonate in combination with a fatty acid salt. Here, as the fatty acid salt, sodium rosinate and potassium rosinate are preferable, and as the alkylbenzenesulfonate, sodium dodecylbenzenesulfonate and potassium dodecylbenzenesulfonate are preferable. In addition, these emulsifiers may be used alone or in combination of two or more.

[0028] As described above, by using at least one selected from the group consisting of alkylbenzenesulfonates, alkyl sulfosuccinates, alkyl sulfates, and polyoxyethylene alkyl ether sulfates in combination with a fatty acid salt, the obtained latex contains at least one selected from the group consisting of alkylbenzenesulfonates, alkyl sulfosuccinates, alkyl sulfates, and polyoxyethylene alkyl ether sulfates, and a fatty acid salt.

[0029] Examples of ionic emulsifiers other than anionic emulsifiers include copolymerizable emulsifiers such as sulfoesters of α,β-unsaturated carboxylic acids, sulfate esters of α,β-unsaturated carboxylic acids, and sulfoalkylaryl ethers.

[0030] Furthermore, nonionic emulsifiers such as polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, polyoxyethylene alkyl esters, and polyoxyethylene sorbitan alkyl esters may also be used in combination, so long as they do not inhibit coagulation by a coagulant used in membrane formation such as dip molding.

[0031] The amount of the emulsifier used in the above production method (1) is preferably 0.1 to 50 parts by weight, more preferably 0.5 to 30 parts by weight, based on 100 parts by weight of synthetic polyisoprene. When two or more kinds of emulsifiers are used, it is preferable that the total amount of these is within the above range. That is, for example, when at least one selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkyl sulfate ester salt, and polyoxyethylene alkyl ether sulfate ester salt is used in combination with a fatty acid salt, it is preferable that the total amount of these is within the above range. By setting the amount of the emulsifier to the above range, the generation of aggregates during emulsification can be further suppressed.

[0032] In addition, when at least one selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkyl sulfate, and polyoxyethylene alkyl ether sulfate is used in combination with a fatty acid salt as an anionic emulsifier, the weight ratio of the "fatty acid salt" to the "total of at least one emulsifier selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkyl sulfate, and polyoxyethylene alkyl ether sulfate" is preferably in the range of 1:1 to 10:1, more preferably in the range of 1:1 to 7:1. By setting the weight ratio of at least one emulsifier selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkyl sulfate, and polyoxyethylene alkyl ether sulfate in the above range, foaming that occurs when handling synthetic polyisoprene can be suppressed, which eliminates the need for operations such as leaving the mixture for a long time or adding an antifoaming agent, leading to improved workability and reduced costs.

[0033] The amount of water used in the above production method (1) is preferably 10 to 1,000 parts by weight, more preferably 30 to 500 parts by weight, and most preferably 50 to 100 parts by weight, relative to 100 parts by weight of the organic solvent solution of synthetic polyisoprene. The type of water used may be hard water, soft water, ion-exchanged water, distilled water, zeolite water, etc., with soft water, ion-exchanged water, and distilled water being preferred.

[0034] The device for emulsifying the solution or fine suspension of synthetic polyisoprene dissolved or finely dispersed in an organic solvent in water in the presence of an emulsifier is not particularly limited, and can be any device that is commercially available as an emulsifier or disperser. The method for adding the emulsifier to the solution or fine suspension of synthetic polyisoprene is not particularly limited, and the emulsifier may be added in advance to either water or the solution or fine suspension of synthetic polyisoprene, or to both, or may be added to the emulsion during the emulsification operation, or may be added all at once or in portions.

[0035] Examples of emulsifying devices include batch emulsifying machines such as "Homogenizer" (manufactured by IKA), "Polytron" (manufactured by Kinematica), and "TK Auto Homo Mixer" (manufactured by Tokushu Kika Kogyo); "TK Pipeline Homo Mixer" (manufactured by Tokushu Kika Kogyo), "Colloid Mill" (manufactured by Kobe Steel Pantech), "Thrasher" (manufactured by Nippon Coke & Engineering Co., Ltd.), "Trigonal Wet Fine Grinding Mill" (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.), "Cavitron" (manufactured by Eurotech), and Examples of such machines include continuous emulsifiers such as "Milder" (manufactured by Pacific Machinery & Engineering Co., Ltd.) and "Fine Flow Mill" (manufactured by Pacific Machinery & Engineering Co., Ltd.); high-pressure emulsifiers such as "Microfluidizer" (manufactured by Mizuho Kogyo Co., Ltd.), "Nanomizer" (manufactured by Nanomizer Co., Ltd.), and "APV Gaulin" (manufactured by Gaulin Co., Ltd.); membrane emulsifiers such as "Membrane Emulsifier" (manufactured by Reika Kogyo Co., Ltd.); vibration emulsifiers such as "Vibro Mixer" (manufactured by Reika Kogyo Co., Ltd.); and ultrasonic emulsifiers such as "Ultrasonic Homogenizer" (manufactured by Branson Co., Ltd.). The conditions for the emulsification operation using an emulsification device are not particularly limited, and the processing temperature, processing time, and the like may be appropriately selected so as to achieve the desired dispersion state.

[0036] In the above production method (1), it is desirable to remove the organic solvent from the emulsion obtained through the emulsification operation. As a method for removing the organic solvent from the emulsion, a method capable of reducing the content of the organic solvent (preferably an alicyclic hydrocarbon solvent or an aliphatic hydrocarbon solvent) in the obtained synthetic polyisoprene latex to 500 ppm by weight or less is preferable, and for example, a method such as reduced pressure distillation, normal pressure distillation, steam distillation, and centrifugation can be adopted.

[0037] Furthermore, after removing the organic solvent, in order to increase the solid content concentration of the synthetic polyisoprene latex, a concentration operation may be carried out by a method such as reduced pressure distillation, normal pressure distillation, centrifugation, membrane concentration, etc., as necessary. In particular, from the viewpoint of increasing the solid content concentration of the synthetic polyisoprene latex and reducing the residual amount of the emulsifier in the synthetic polyisoprene latex, it is preferable to carry out centrifugation.

[0038] The centrifugation is preferably carried out using a continuous centrifuge under the conditions of a centrifugal force of preferably 100 to 10,000 G, a solids concentration of the synthetic polyisoprene latex before centrifugation of preferably 2 to 15% by weight, a flow rate of the centrifuge of preferably 500 to 1700 kg / hr, and a back pressure (gauge pressure) of the centrifuge of preferably 0.03 to 1.6 MPa, and a synthetic polyisoprene latex can be obtained as a light liquid after centrifugation. This can reduce the amount of emulsifier remaining in the synthetic polyisoprene latex.

[0039] The synthetic polyisoprene latex may further contain additives that are commonly used in the field of latex, such as a pH adjuster, an antifoaming agent, a preservative, a crosslinking agent, a chelating agent, an oxygen scavenger, a dispersant, and an antioxidant.

[0040] Examples of pH adjusters include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide; alkali metal carbonates such as sodium carbonate and potassium carbonate; alkali metal bicarbonates such as sodium bicarbonate; ammonia; and organic amine compounds such as trimethylamine and triethanolamine; with alkali metal hydroxides or ammonia being preferred.

[0041] As described above, the latex of the water-insoluble conjugated diene polymer (A) may be a latex of a styrene-isoprene-styrene block copolymer (SIS), where "S" represents a styrene block and "I" represents an isoprene block.

[0042] The SIS contained in the SIS latex can be obtained by a conventional method, for example, block copolymerization of isoprene and styrene in an inert polymerization solvent using an active organic metal such as n-butyl lithium as an initiator. The obtained SIS polymer solution can be used as it is for the production of the SIS latex, but the solid SIS can also be taken out of the polymer solution, and then dissolved in an organic solvent to be used for the production of the SIS latex. The method for producing the SIS latex is not particularly limited, but a method in which a solution or fine suspension of SIS dissolved or finely dispersed in an organic solvent is emulsified in water in the presence of an emulsifier, and the organic solvent is removed as necessary to produce the SIS latex is preferred. In this case, impurities such as the residue of the polymerization catalyst remaining in the polymer solution after synthesis may be removed. In addition, an antioxidant, which will be described later, may be added to the solution during or after polymerization. Commercially available solid SIS may also be used.

[0043] As the organic solvent, the same ones as in the case of the synthetic polyisoprene can be used, and aromatic hydrocarbon solvents and alicyclic hydrocarbon solvents are preferred, with cyclohexane and toluene being particularly preferred. The amount of the organic solvent used is usually 50 to 2,000 parts by weight, preferably 80 to 1,000 parts by weight, more preferably 100 to 500 parts by weight, and further preferably 150 to 300 parts by weight, based on 100 parts by weight of the SIS.

[0044] Examples of the emulsifier include the same ones as those in the case of the synthetic polyisoprene, and anionic emulsifiers are preferred, with potassium rosinate and sodium dodecylbenzenesulfonate being particularly preferred.

[0045] The amount of the emulsifier used is preferably 0.1 to 50 parts by weight, more preferably 0.5 to 30 parts by weight, based on 100 parts by weight of the SIS. By setting the amount of the emulsifier used within the above range, the stability of the obtained latex can be improved.

[0046] The amount of water used in the above-mentioned SIS latex production method is preferably 10 to 1,000 parts by weight, more preferably 30 to 500 parts by weight, and most preferably 50 to 100 parts by weight, based on 100 parts by weight of the SIS organic solvent solution. The type of water used may include hard water, soft water, ion-exchanged water, distilled water, zeolite water, etc. Also, a polar solvent, typified by an alcohol such as methanol, may be used in combination with water.

[0047] The apparatus for emulsifying the organic solvent solution or fine suspension of SIS in water in the presence of an emulsifier can be the same as that for the synthetic polyisoprene. The method of adding the emulsifier is not particularly limited, and it may be added in advance to either the water or the organic solvent solution or fine suspension of SIS, or to both, or it may be added to the emulsion during the emulsification operation, or it may be added all at once or in portions.

[0048] In the above-mentioned method for producing SIS latex, it is preferable to obtain SIS latex by removing the organic solvent from the emulsion obtained through the emulsification operation. The method for removing the organic solvent from the emulsion is not particularly limited, and methods such as reduced pressure distillation, normal pressure distillation, steam distillation, and centrifugation can be adopted.

[0049] After removing the organic solvent, the SIS latex may be concentrated by vacuum distillation, atmospheric distillation, centrifugation, membrane concentration or the like, if necessary, in order to increase the solids concentration of the SIS latex.

[0050] In addition, the SIS latex may contain additives such as pH adjusters, antifoamers, preservatives, crosslinking agents, chelating agents, oxygen scavengers, dispersants, and antioxidants, which are generally used in the field of latex. Examples of pH adjusters include those similar to those in the case of synthetic polyisoprene, and alkali metal hydroxides or ammonia are preferred. The pH of the SIS latex is not particularly limited, but as described below, when a latex composition is made using the SIS latex or the like and the latex composition is aged under a specified condition, it is preferred that the pH of the latex composition before aging is 10 or more.

[0051] The content of styrene units in the styrene block in the SIS contained in the SIS latex thus obtained is preferably 70 to 100% by weight, more preferably 90 to 100% by weight, and further preferably 100% by weight, based on the total monomer units. The content of isoprene units in the isoprene block in the SIS is preferably 70 to 100% by weight, more preferably 90 to 100% by weight, and further preferably 100% by weight, based on the total monomer units. The content ratio of styrene units and isoprene units in SIS, in terms of the weight ratio of "styrene units:isoprene units", is usually in the range of 1:99 to 90:10, preferably 3:97 to 70:30, more preferably 5:95 to 50:50, and further preferably 10:90 to 30:70.

[0052] The weight-average molecular weight of the SIS, calculated as standard polystyrene by gel permeation chromatography analysis, is preferably 10,000 to 1,000,000, more preferably 50,000 to 500,000, and further preferably 100,000 to 300,000. By setting the weight-average molecular weight of the SIS within the above range, the balance between the tensile strength and flexibility of the obtained film molded product such as a dip molded product is improved, and the production of a SIS latex tends to be easier.

[0053] As the latex of the water-insoluble conjugated diene polymer (A), as described above, a latex of a nitrile group-containing conjugated diene copolymer can also be used.

[0054] The nitrile group-containing conjugated diene copolymer is a copolymer obtained by copolymerizing a conjugated diene monomer with an ethylenically unsaturated nitrile monomer, and may also be a copolymer obtained by copolymerizing, in addition to the above, other ethylenically unsaturated monomers copolymerizable therewith, which are used as necessary.

[0055] Examples of the conjugated diene monomer include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, and chloroprene. Among these, 1,3-butadiene and isoprene are preferred, and 1,3-butadiene is more preferred. These conjugated diene monomers can be used alone or in combination of two or more. The content of the conjugated diene monomer unit formed by the conjugated diene monomer in the nitrile group-containing conjugated diene copolymer is preferably 56 to 78% by weight, more preferably 56 to 73% by weight, and even more preferably 56 to 68% by weight. By setting the content of the conjugated diene monomer unit within the above range, the obtained film molded product such as a dip molded product can be made to have sufficient tensile strength and excellent texture and elongation.

[0056] The ethylenically unsaturated nitrile monomer is not particularly limited as long as it is an ethylenically unsaturated monomer containing a nitrile group, and examples thereof include acrylonitrile, methacrylonitrile, fumaronitrile, α-chloroacrylonitrile, α-cyanoethylacrylonitrile, etc. Among them, acrylonitrile and methacrylonitrile are preferred, and acrylonitrile is more preferred. These ethylenically unsaturated nitrile monomers can be used alone or in combination of two or more. The content ratio of the ethylenically unsaturated nitrile monomer unit formed by the ethylenically unsaturated nitrile monomer in the nitrile group-containing conjugated diene copolymer is preferably 20 to 40% by weight, more preferably 25 to 40% by weight, and even more preferably 30 to 40% by weight. By setting the content of the ethylenically unsaturated nitrile monomer unit within the above range, the obtained film molded product such as a dip molded product can be made to have sufficient tensile strength while being excellent in texture and elongation.

[0057] Examples of other ethylenically unsaturated monomers copolymerizable with the conjugated diene monomer and the ethylenically unsaturated nitrile monomer include ethylenically unsaturated carboxylic acid monomers, which are ethylenically unsaturated monomers containing a carboxyl group; vinyl aromatic monomers such as styrene, alkylstyrene, and vinylnaphthalene; fluoroalkyl vinyl ethers such as fluoroethyl vinyl ether; ethylenically unsaturated amide monomers such as (meth)acrylamide, N-methylol (meth)acrylamide, N,N-dimethylol (meth)acrylamide, N-methoxymethyl (meth)acrylamide, and N-propoxymethyl (meth)acrylamide; methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, dibutyl maleate, and fumarate. Examples of the ethylenically unsaturated carboxylic acid ester monomers include dibutyl acrylate, diethyl maleate, methoxymethyl (meth)acrylate, ethoxyethyl (meth)acrylate, methoxyethoxyethyl (meth)acrylate, cyanomethyl (meth)acrylate, 2-cyanoethyl (meth)acrylate, 1-cyanopropyl (meth)acrylate, 2-ethyl-6-cyanohexyl (meth)acrylate, 3-cyanopropyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, glycidyl (meth)acrylate, and dimethylaminoethyl (meth)acrylate; and crosslinkable monomers such as divinylbenzene, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol (meth)acrylate. These ethylenically unsaturated monomers can be used alone or in combination of two or more.

[0058] The ethylenically unsaturated carboxylic acid monomer is not particularly limited as long as it is an ethylenically unsaturated monomer containing a carboxyl group, and examples thereof include ethylenically unsaturated monocarboxylic acid monomers such as acrylic acid and methacrylic acid; ethylenically unsaturated polyvalent carboxylic acid monomers such as itaconic acid, maleic acid, and fumaric acid; ethylenically unsaturated polyvalent carboxylic acid anhydrides such as maleic anhydride and citraconic anhydride; ethylenically unsaturated polyvalent carboxylic acid partial ester monomers such as monobutyl fumarate, monobutyl maleate, and mono-2-hydroxypropyl maleate; and the like. Among these, ethylenically unsaturated monocarboxylic acids are preferred, and methacrylic acid is particularly preferred. These ethylenically unsaturated carboxylic acid monomers can also be used as alkali metal salts or ammonium salts. Moreover, the ethylenically unsaturated carboxylic acid monomers can be used alone or in combination of two or more. The content of ethylenically unsaturated carboxylic acid monomer units formed by ethylenically unsaturated carboxylic acid monomers in the nitrile group-containing conjugated diene copolymer is preferably 2 to 5% by weight, more preferably 2 to 4.5% by weight, and further preferably 2.5 to 4.5% by weight. By setting the content of the ethylenically unsaturated carboxylic acid monomer units within the above range, the obtained film molded product such as a dip molded product can be made to have sufficient tear strength and excellent texture.

[0059] In the nitrile group-containing conjugated diene copolymer, the content of other monomer units formed by other ethylenically unsaturated monomers is preferably 10% by weight or less, more preferably 5% by weight or less, and even more preferably 3% by weight or less.

[0060] The nitrile group-containing conjugated diene copolymer can be obtained by copolymerizing a monomer mixture containing the above-mentioned monomers, and a method of copolymerizing by emulsion polymerization is preferred. As the emulsion polymerization method, a conventionally known method can be adopted.

[0061] When the monomer mixture containing the above-mentioned monomers is emulsion-polymerized, it is possible to use commonly used polymerization auxiliary materials such as an emulsifier, a polymerization initiator, a molecular weight regulator, etc. The method of adding these polymerization auxiliary materials is not particularly limited, and any method such as initial lump-sum addition, divided addition, or continuous addition may be used.

[0062] The emulsifier is not particularly limited, but examples thereof include nonionic emulsifiers such as polyoxyethylene alkyl ether, polyoxyethylene alkylphenol ether, polyoxyethylene alkyl ester, and polyoxyethylene sorbitan alkyl ester; anionic emulsifiers such as alkylbenzene sulfonate salts such as potassium dodecylbenzene sulfonate and sodium dodecylbenzene sulfonate, higher alcohol sulfate salts, and alkyl sulfosuccinate salts; cationic emulsifiers such as alkyltrimethylammonium chloride, dialkylammonium chloride, and benzylammonium chloride; and copolymerizable emulsifiers such as sulfoesters of α,β-unsaturated carboxylic acids, sulfate esters of α,β-unsaturated carboxylic acids, and sulfoalkylaryl ethers. Among these, anionic emulsifiers are preferred, alkylbenzene sulfonates are more preferred, and potassium dodecylbenzene sulfonate and sodium dodecylbenzene sulfonate are particularly preferred. These emulsifiers can be used alone or in combination of two or more. The amount of emulsifier used is preferably 0.1 to 10 parts by weight based on 100 parts by weight of the monomer mixture.

[0063] The polymerization initiator is not particularly limited, but examples thereof include inorganic peroxides such as sodium persulfate, potassium persulfate, ammonium persulfate, potassium perphosphate, and hydrogen peroxide; organic peroxides such as diisopropylbenzene hydroperoxide, cumene hydroperoxide, t-butyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, di-t-butyl peroxide, di-α-cumyl peroxide, acetyl peroxide, isobutyryl peroxide, and benzoyl peroxide; and azo compounds such as azobisisobutyronitrile, azobis-2,4-dimethylvaleronitrile, and methyl azobisisobutyrate. These polymerization initiators can be used alone or in combination of two or more kinds. The amount of the polymerization initiator used is preferably 0.01 to 10 parts by weight, more preferably 0.01 to 2 parts by weight, based on 100 parts by weight of the monomer mixture.

[0064] The peroxide initiator can be used as a redox polymerization initiator in combination with a reducing agent. The reducing agent is not particularly limited, but includes compounds containing reduced metal ions such as ferrous sulfate and cuprous naphthenate; sulfonic acid compounds such as sodium methanesulfonate; and amine compounds such as dimethylaniline. These reducing agents can be used alone or in combination of two or more. The amount of the reducing agent used is preferably 3 to 1000 parts by weight per 100 parts by weight of the peroxide.

[0065] The amount of water used in emulsion polymerization is preferably from 80 to 600 parts by weight, particularly preferably from 100 to 200 parts by weight, based on 100 parts by weight of the total monomers used.

[0066] Examples of the method of adding the monomers include a method of adding the monomers to be used in a reaction vessel all at once, a method of adding them continuously or intermittently as the polymerization proceeds, a method of adding a part of the monomers and reacting them to a specific conversion rate, and then polymerizing by adding the remaining monomers continuously or intermittently, and any of these methods may be adopted. When the monomers are mixed and added continuously or intermittently, the composition of the mixture may be constant or may be changed. In addition, the various monomers to be used may be mixed in advance and then added to the reaction vessel, or each monomer may be added to the reaction vessel separately.

[0067] Furthermore, if necessary, polymerization auxiliary materials such as a chelating agent, a dispersing agent, a pH adjuster, an oxygen scavenger, and a particle size adjuster can be used, and the type and the amount of these are not particularly limited.

[0068] The polymerization temperature when carrying out the emulsion polymerization is not particularly limited, but is usually 3 to 95° C., and preferably 5 to 60° C. The polymerization time is about 5 to 40 hours.

[0069] As described above, the monomer mixture is emulsion-polymerized, and when a predetermined polymerization conversion rate is reached, the polymerization reaction is terminated by cooling the polymerization system or adding a polymerization terminator. The polymerization conversion rate at the time of terminating the polymerization reaction is preferably 90% by weight or more, more preferably 93% by weight or more.

[0070] The polymerization terminator is not particularly limited, but examples thereof include hydroxylamine, hydroxylamine sulfate, diethylhydroxylamine, hydroxylamine sulfonic acid and its alkali metal salts, sodium dimethyldithiocarbamate, hydroquinone derivatives, catechol derivatives, and aromatic hydroxydithiocarboxylic acids such as hydroxydimethylbenzenethiocarboxylic acid, hydroxydiethylbenzenedithiocarboxylic acid, and hydroxydibutylbenzenedithiocarboxylic acid, and their alkali metal salts. The amount of the polymerization terminator used is preferably 0.05 to 2 parts by weight based on 100 parts by weight of the monomer mixture.

[0071] After the polymerization reaction is terminated, if desired, unreacted monomers are removed and the solid content and pH are adjusted to obtain a latex of a nitrile group-containing conjugated diene copolymer.

[0072] Furthermore, to the latex of the nitrile group-containing conjugated diene copolymer, an antioxidant, a preservative, an antibacterial agent, a dispersant, etc. may be appropriately added, if necessary.

[0073] As described above, the latex of the water-insoluble conjugated diene polymer (A) may be a latex of natural rubber from which proteins have been removed (deproteinized natural rubber). The deproteinized natural rubber latex may be what is known as "deproteinized natural rubber latex," which is obtained by a known protein removal method, such as a method in which proteins in natural rubber latex are decomposed with a protease or a surfactant, and then removed by washing or centrifugation.

[0074] As described above, the water-insoluble conjugated diene polymer (A) used in the present invention may be synthetic polyisoprene, styrene-isoprene-styrene block copolymer (SIS), nitrile group-containing conjugated diene copolymer, deproteinized natural rubber, or the like. However, the present invention is not limited to these, and a butadiene polymer, a styrene-butadiene copolymer, or the like may also be used.

[0075] The butadiene polymer may be a homopolymer of 1,3-butadiene as a conjugated diene monomer, or a copolymer obtained by copolymerizing 1,3-butadiene as a conjugated diene monomer with another ethylenically unsaturated monomer that is copolymerizable with the conjugated diene monomer.

[0076] The styrene-butadiene copolymer is a copolymer obtained by copolymerizing styrene with 1,3-butadiene as a conjugated diene monomer, and may also be a copolymer obtained by copolymerizing, in addition to these, other ethylenically unsaturated monomers copolymerizable therewith, which are used as necessary.

[0077] In addition, the water-insoluble conjugated diene polymer (A) used in the present invention may be an acid-modified water-insoluble conjugated diene polymer (A) obtained by modification with a monomer having an acidic group, or may be a carboxy-modified water-insoluble conjugated diene polymer (A) as long as it shows water insolubility. The carboxy-modified water-insoluble conjugated diene polymer (A) can be obtained by modifying the above-mentioned water-insoluble conjugated diene polymer (A) with a monomer having a carboxyl group. In addition, when an ethylenically unsaturated carboxylic acid monomer is used as the possible other ethylenically unsaturated monomer for the nitrile group-containing conjugated diene copolymer, the copolymer is already carboxy-modified, and therefore modification with a monomer having a carboxyl group described below is not necessarily required.

[0078] The method for modifying the water-insoluble conjugated diene polymer (A) with a monomer having a carboxyl group is not particularly limited, but for example, a method of graft polymerizing the water-insoluble conjugated diene polymer (A) with a monomer having a carboxyl group in an aqueous phase can be mentioned. The method for graft polymerizing the monomer having a carboxyl group in an aqueous phase is not particularly limited, and a conventionally known method may be used, but for example, a method of adding the monomer having a carboxyl group and a graft polymerization catalyst to the latex of the water-insoluble conjugated diene polymer (A), and then reacting the monomer having a carboxyl group with the water-insoluble conjugated diene polymer (A) in the aqueous phase is preferred.

[0079] The graft polymerization catalyst is not particularly limited, but examples thereof include inorganic peroxides such as sodium persulfate, potassium persulfate, ammonium persulfate, potassium perphosphate, and hydrogen peroxide; organic peroxides such as diisopropylbenzene hydroperoxide, cumene hydroperoxide, t-butyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, di-t-butyl peroxide, isobutyryl peroxide, and benzoyl peroxide; and azo compounds such as 2,2'-azobisisobutyronitrile, azobis-2,4-dimethylvaleronitrile, and methyl azobisisobutyrate; and the like. From the viewpoint of further improving the tensile strength of the resulting film molded body such as a dip molded body, organic peroxides are preferred, and 1,1,3,3-tetramethylbutyl hydroperoxide is particularly preferred. These graft polymerization catalysts may be used alone or in combination of two or more.

[0080] The above graft polymerization catalysts can be used alone or in combination of two or more kinds. The amount of the graft polymerization catalyst used varies depending on the type, but is preferably 0.1 to 10 parts by weight, more preferably 0.2 to 5 parts by weight, based on 100 parts by weight of the water-insoluble conjugated diene polymer (A). The method of adding the graft polymerization catalyst is not particularly limited, and known methods of addition such as lump-sum addition, divided addition, and continuous addition can be adopted.

[0081] In addition, the organic peroxide can be used as a redox polymerization initiator in combination with a reducing agent. The reducing agent is not particularly limited, but examples thereof include sodium formaldehyde sulfoxylate (SFS), hydrosulfite, dimethylamine, ascorbic acid, sucrose, and ferrous sulfate. These reducing agents may be used alone or in combination of two or more.

[0082] The amount of the reducing agent to be added is not particularly limited, but is preferably 0.01 to 1 part by weight per 1 part by weight of the organic peroxide.

[0083] The method of adding the organic peroxide and the reducing agent is not particularly limited, and known methods of addition such as lump-sum addition, divided addition, continuous addition, etc. can be used.

[0084] The reaction temperature when reacting the water-insoluble conjugated diene polymer (A) with the monomer having a carboxyl group is not particularly limited, but is preferably 15 to 80° C., more preferably 30 to 50° C. The reaction time when reacting the water-insoluble conjugated diene polymer (A) with the monomer having a carboxyl group may be appropriately set depending on the reaction temperature, but is preferably 30 to 300 minutes, more preferably 60 to 120 minutes.

[0085] When the water-insoluble conjugated diene polymer (A) is reacted with a monomer having a carboxyl group, the solid content concentration of the latex of the water-insoluble conjugated diene polymer (A) is not particularly limited, but is preferably 5 to 60% by weight, more preferably 10 to 40% by weight.

[0086] Examples of monomers having a carboxyl group include ethylenically unsaturated monocarboxylic acid monomers such as acrylic acid and methacrylic acid; ethylenically unsaturated polycarboxylic acid monomers such as itaconic acid, maleic acid, fumaric acid, and butene tricarboxylic acid; partial ester monomers of ethylenically unsaturated polycarboxylic acids such as monobutyl fumarate, monobutyl maleate, and mono 2-hydroxypropyl maleate; and polycarboxylic anhydrides such as maleic anhydride and citraconic anhydride. Since the effect of carboxy modification is more pronounced, ethylenically unsaturated monocarboxylic acid monomers are preferred, acrylic acid and methacrylic acid are more preferred, and methacrylic acid is particularly preferred. These monomers may be used alone or in combination of two or more. The carboxyl group also includes salts with alkali metals, ammonia, and the like.

[0087] The amount of the monomer having a carboxyl group used is preferably 0.01 to 100 parts by weight, more preferably 0.01 to 40 parts by weight, even more preferably 0.5 to 20 parts by weight, and even more preferably 2 to 5 parts by weight, based on 100 parts by weight of the water-insoluble conjugated diene polymer (A). By setting the amount of the monomer having a carboxyl group used within the above range, the viscosity of the latex composition becomes more appropriate, making it easier to transport, and further improving the tear strength of the resulting film molded product such as a dip molded product.

[0088] The method of adding the monomer having a carboxyl group to the latex of the water-insoluble conjugated diene polymer (A) is not particularly limited, and any known addition method such as lump-sum addition, divided addition, or continuous addition can be used.

[0089] The modification rate of the carboxy-modified water-insoluble conjugated diene polymer (A) with a monomer having a carboxyl group may be appropriately controlled depending on the intended use of the resulting film molded article such as a dip-molded article, so long as the polymer shows water-insolubility, but is preferably 0.01 to 10% by weight, more preferably 0.2 to 5% by weight, even more preferably 0.3 to 3% by weight, even more preferably 0.4 to 2% by weight, and particularly preferably 0.4 to 1% by weight. The modification rate is expressed by the following formula: Modification rate (wt%) = (X / Y) x 100 In the above formula, X represents the weight of the unit of the monomer having a carboxyl group in the carboxy-modified water-insoluble conjugated diene polymer (A), and Y represents the weight of the carboxy-modified water-insoluble conjugated diene polymer (A). X represents the weight of the carboxy-modified water-insoluble conjugated diene polymer (A), 1 H-NMR measurement was performed. 1 It can be determined by a method of calculation from the results of H-NMR measurement, or a method of determining the amount of acid by neutralization titration and then calculating from the determined amount of acid.

[0090] The latex of the water-insoluble conjugated diene polymer (A) (including an acid-modified water-insoluble conjugated diene polymer (A)) used in the present invention may contain additives that are usually added in the field of latexes, such as a pH adjuster, an antifoaming agent, a preservative, a chelating agent, an oxygen scavenger, a dispersant, and an antioxidant.

[0091] Examples of pH adjusters include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide; alkali metal carbonates such as sodium carbonate and potassium carbonate; alkali metal bicarbonates such as sodium bicarbonate; ammonia; and organic amine compounds such as trimethylamine and triethanolamine; with alkali metal hydroxides or ammonia being preferred.

[0092] The solid content of the latex of the water-insoluble conjugated diene polymer (A) (containing the acid-modified water-insoluble conjugated diene polymer (A)) used in the present invention is preferably 30 to 70% by weight, more preferably 40 to 70% by weight, and further preferably 50 to 70% by weight. By setting the solid content within the above range, the generation of aggregates in the latex can be more effectively suppressed, and separation of polymer particles during storage of the latex can be more effectively suppressed.

[0093] The latex composition of the present invention contains, in addition to the above-mentioned water-insoluble conjugated diene polymer (A) latex, a latex of an alkali-soluble conjugated diene polymer (B) having an absorbance of less than 0.3 at pH=8 and a solid content of 3% by weight.

[0094] According to the present invention, by adding the latex of the alkali-soluble conjugated diene polymer (B) having an absorbance of less than 0.3 at pH=8 and solid content concentration of 3% by weight in addition to the water-insoluble conjugated diene polymer (A) described above, the film-formed product such as the dip-molded product obtained by using such a latex composition can have high tear strength, and such a film-formed product such as the dip-molded product having high tear strength can be obtained at a relatively low temperature and in a short maturation time. Therefore, according to the present invention, excellent productivity can be realized by shortening the maturation time.

[0095] The latex of alkali-soluble conjugated diene polymer (B) having an absorbance of less than 0.3 at pH=8 and solid content concentration of 3% by weight (hereinafter referred to as "latex of alkali-soluble conjugated diene polymer (B)") is obtained by emulsion polymerization of a monomer mixture containing a conjugated diene monomer and a water-soluble monomer, and is a latex of a conjugated diene polymer that exhibits solubility or affinity in an alkaline aqueous solution. The absorbance of the latex of alkali-soluble conjugated diene polymer (B) at pH=8 and solid content concentration of 3% by weight can be measured as the absorbance at 500 nm by a spectrophotometer at a temperature of 25°C, for example, by adding a pH adjuster such as sulfuric acid, nitric acid, sodium hydroxide, or potassium hydroxide and water to the latex of alkali-soluble conjugated diene polymer (B) to adjust the pH to 8 and the solid content concentration to 3% by weight.

[0096] The latex of the alkali-soluble conjugated diene polymer (B) may have an absorbance of less than 0.3, preferably 0.1 or less, more preferably 0.05 or less at a solids concentration of 3% by weight at pH=8, and may be water-soluble at pH=8. However, it is desirable that the absorbance is less than 0.3, preferably 0.1 or less, more preferably 0.05 or less at a solids concentration of 3% by weight in a pH range of 8 or more, and that the latex has solubility or affinity in an alkaline aqueous solution of pH=8 or more.

[0097] On the other hand, the latex of the alkali-soluble conjugated diene polymer (B) preferably does not exhibit solubility or affinity in water as a medium at a pH of 6 or less. That is, the latex of the alkali-soluble conjugated diene polymer (B) is preferably configured such that particles of the alkali-soluble conjugated diene polymer (B) having a volume average particle diameter preferably in the range of 60 to 200 nm are dispersed in water as a medium at a pH of 6 or less, and preferably configured such that particles of the alkali-soluble conjugated diene polymer (B) having a volume average particle diameter in the range of 60 to 200 nm are dispersed in water as a medium in an acidic pH range of 6 or less. That is, the latex of the alkali-soluble conjugated diene polymer (B) used in the present invention preferably contains particles of the alkali-soluble conjugated diene polymer (B) in a dispersed state in water as a medium at pH=6 or less, thereby maintaining the latex state, while at pH=8 or more, the particles of the alkali-soluble conjugated diene polymer (B) are dissolved or hydrated in the water as a medium, thereby exhibiting the properties of an aqueous solution. The volume average particle diameter of the particles of the alkali-soluble conjugated diene polymer (B) is preferably 60 to 130 nm, more preferably 60 to 100 nm.

[0098] Such a latex of the alkali-soluble conjugated diene polymer (B) is obtained by emulsion polymerization of a monomer mixture containing a conjugated diene monomer and a water-soluble monomer, that is, a copolymer of the conjugated diene monomer and the water-soluble monomer obtained by copolymerizing the conjugated diene monomer and the water-soluble monomer.

[0099] Examples of the conjugated diene monomer include butadiene, isoprene, chloroprene, and 1,3-pentadiene, and among these, isoprene is preferred from the viewpoint of increasing the tear strength of the resulting film molded article such as a dip molded article. These monomers may be used alone or in combination of two or more.

[0100] The content of the conjugated diene monomer units in the alkali-soluble conjugated diene polymer (B) constituting the latex of the alkali-soluble conjugated diene polymer (B) is preferably 20 to 80% by weight, more preferably 30 to 75% by weight, and even more preferably 40 to 50% by weight, based on 100% by weight of all monomer units. By setting the content of the conjugated diene monomer units within the above range, the solubility and affinity of the alkali-soluble conjugated diene polymer (B) in water having a pH of 8 or more can be sufficiently ensured, while the tear strength of the resulting film molded article such as a dip molded article can be further increased.

[0101] The water-soluble monomer is not particularly limited as long as it is a compound that can be copolymerized with the conjugated diene monomer and exhibits hydrophilicity, but a monomer having an acidic group is preferred, and a monomer having a carboxyl group is more preferred. Examples of the monomer having a carboxyl group include ethylenically unsaturated monocarboxylic acid monomers such as acrylic acid and methacrylic acid; ethylenically unsaturated polycarboxylic acid monomers such as itaconic acid, maleic acid, fumaric acid, and butene tricarboxylic acid; partial ester monomers of ethylenically unsaturated polycarboxylic acids such as monobutyl fumarate, monobutyl maleate, and mono 2-hydroxypropyl maleate; polycarboxylic anhydrides such as maleic anhydride and citraconic anhydride; and the like. From the viewpoint of being able to further increase the tear strength of a film-formed body such as a dip-formed body, an ethylenically unsaturated monocarboxylic acid monomer is preferred, acrylic acid and methacrylic acid are more preferred, and methacrylic acid is particularly preferred. These monomers may be used alone or in combination of two or more.

[0102] The content of the water-soluble monomer units in the alkali-soluble conjugated diene polymer (B) constituting the latex of the alkali-soluble conjugated diene polymer (B) is preferably 20 to 80% by weight, more preferably 25 to 70% by weight, and even more preferably 50 to 60% by weight, based on 100% by weight of all monomer units. By setting the content of the water-soluble monomer units within the above range, the solubility and affinity of the alkali-soluble conjugated diene polymer (B) in water having a pH of 8 or more can be sufficiently ensured, while the tear strength of the resulting film molded product such as a dip molded product can be further increased.

[0103] In addition, the latex of the alkali-soluble conjugated diene polymer (B) may be obtained by emulsion polymerization of a monomer mixture containing a conjugated diene monomer and a water-soluble monomer, as well as an ethylenically unsaturated monomer copolymerizable therewith. Examples of such copolymerizable monomers include vinyl aromatic monomers, fluoroalkyl vinyl ethers, ethylenically unsaturated amide monomers, ethylenically unsaturated carboxylic acid ester monomers, and crosslinkable monomers, and specific examples thereof include those mentioned above. These ethylenically unsaturated monomers can be used alone or in combination of two or more.

[0104] The content of units of copolymerizable ethylenically unsaturated monomer in the alkali-soluble conjugated diene polymer (B) constituting the latex of the alkali-soluble conjugated diene polymer (B) is preferably 10% by weight or less, more preferably 3% by weight or less, based on 100% by weight of all monomer units.

[0105] When emulsion polymerizing a monomer mixture containing a conjugated diene monomer, a water-soluble monomer, and an ethylenically unsaturated monomer that is copolymerizable as required, it is possible to use commonly used polymerization auxiliary materials such as an emulsifier, a polymerization initiator, a molecular weight regulator, etc. The method of adding these polymerization auxiliary materials is not particularly limited, and any method such as an initial lump addition method, a divided addition method, or a continuous addition method may be used.

[0106] The emulsifier, polymerization initiator, and molecular weight modifier are not particularly limited, but the same ones as those in the case of the latex of the nitrile group-containing conjugated diene copolymer described above can be used, and the amount of use can be the same.In addition, when a peroxide initiator is used as the polymerization initiator, it can be used as a redox polymerization initiator in combination with a reducing agent, and the same ones as those in the case of the latex of the nitrile group-containing conjugated diene copolymer described above can be used as the reducing agent, and the amount of use can be the same.

[0107] The amount of water used in emulsion polymerization is preferably from 80 to 600 parts by weight, particularly preferably from 100 to 200 parts by weight, based on 100 parts by weight of the total monomers used.

[0108] Examples of the method of adding the monomer include a method of adding the monomers to be used in a reaction vessel all at once, a method of adding them continuously or intermittently as the polymerization proceeds, a method of adding a part of the monomers and reacting them to a specific conversion rate, and then adding the remaining monomers continuously or intermittently to polymerize them, and any of these methods may be adopted. When the monomers are mixed and added continuously or intermittently, the composition of the mixture may be constant or may be changed. In addition, each monomer may be added to the reaction vessel after mixing the various monomers to be used in advance, or may be added to the reaction vessel separately. Furthermore, from the viewpoint of stably performing the emulsion polymerization and obtaining the latex of the alkali-soluble conjugated diene polymer (B) in a latex state, the emulsion polymerization is preferably performed under conditions of pH=7 or less, and more preferably under conditions of pH=2 to 5.

[0109] Furthermore, if necessary, polymerization auxiliary materials such as a chelating agent, a dispersing agent, a pH adjuster, an oxygen scavenger, and a particle size adjuster can be used, and the type and the amount of these are not particularly limited.

[0110] The polymerization temperature when carrying out the emulsion polymerization is not particularly limited, but is usually 3 to 95° C., and preferably 5 to 60° C. The polymerization time is about 5 to 40 hours.

[0111] The weight average molecular weight of the alkali-soluble conjugated diene polymer (B) constituting the latex of the alkali-soluble conjugated diene polymer (B) is preferably 20,000 to 1,000,000, more preferably 150,000 to 600,000, and even more preferably 200,000 to 350,000, as calculated in terms of standard polystyrene by gel permeation chromatography analysis. By setting the weight average molecular weight of the alkali-soluble conjugated diene polymer (B) within the above range, the tear strength of the resulting film molded article, such as a dip molded article, can be further increased.

[0112] The solid content concentration of the latex of the alkali-soluble conjugated diene polymer (B) used in the present invention is preferably 1 to 50% by weight, more preferably 1.5 to 30% by weight, and further preferably 2 to 10% by weight.

[0113] The content of the latex of the alkali-soluble conjugated diene polymer (B) in the latex composition of the present invention is preferably 0.01 to 2 parts by weight, more preferably 0.1 to 1 part by weight, and even more preferably 0.5 to 1 part by weight, relative to 100 parts by weight of the water-insoluble conjugated diene polymer (A) contained in the latex of the water-insoluble conjugated diene polymer (A).

[0114] In addition, the latex composition of the present invention preferably further contains a sulfur-based vulcanizing agent. The sulfur-based vulcanizing agent is not particularly limited, but examples thereof include powdered sulfur, sulfur flowers, precipitated sulfur, colloidal sulfur, surface-treated sulfur, insoluble sulfur, and other sulfur; sulfur chloride, sulfur dichloride, morpholine disulfide, alkylphenol disulfide, caprolactam disulfide (N,N'-dithio-bis(hexahydro-2H-azepinone-2)), phosphorus-containing polysulfide, polymer polysulfide, and sulfur-containing compounds such as 2-(4'-morpholinodithio)benzothiazole. Among these, sulfur is preferably used. The sulfur-based vulcanizing agent can be used alone or in combination of two or more.

[0115] The amount of the sulfur-based vulcanizing agent used is not particularly limited, but is preferably 0.1 to 10 parts by weight, more preferably 0.2 to 3 parts by weight, based on 100 parts by weight of the water-insoluble conjugated diene polymer (A) contained in the latex composition. By setting the content of the sulfur-based vulcanizing agent within the above range, the tear strength of the obtained film molded article such as a dip molded article can be further increased.

[0116] Further, a vulcanization accelerator may be further added to the latex composition. As the vulcanization accelerator, those generally used in dip molding can be used, for example, xanthogen compounds such as xanthogen acid, xanthogen salts, xanthogen disulfide (a compound in which two xanthogen acids are bonded via a sulfur atom or the like), and xanthogen polysulfide (a compound in which three or more xanthogen acids are bonded via a sulfur atom or the like); dithiocarbamic acid such as diethyldithiocarbamic acid, dibutyldithiocarbamic acid, di-2-ethylhexyldithiocarbamic acid, dicyclohexyldithiocarbamic acid, diphenyldithiocarbamic acid, and dibenzyldithiocarbamic acid; Examples of suitable vulcanizing accelerators include 2-mercaptobenzothiazole, zinc 2-mercaptobenzothiazole, 2-mercaptothiazoline, dibenzothiazyl disulfide, 2-(2,4-dinitrophenylthio)benzothiazole, 2-(N,N-diethylthio carbylthio)benzothiazole, 2-(2,6-dimethyl-4-morpholinothio)benzothiazole, 2-(4'-morpholino dithio)benzothiazole, 4-morpholinyl-2-benzothiazyl disulfide, and 1,3-bis(2-benzothiazyl mercaptomethyl)urea. From the viewpoint of suppressing the occurrence of symptoms of delayed-type allergy (Type IV), xanthogen compounds are preferred, with zinc diisopropyl xanthogenate and zinc dibutyl xanthogenate being more preferred, and zinc diisopropyl xanthogenate being particularly preferred. The vulcanization accelerators can be used alone or in combination of two or more.

[0117] The amount of the vulcanization accelerator used is preferably 0.05 to 5 parts by weight, more preferably 0.1 to 2 parts by weight, based on 100 parts by weight of the water-insoluble conjugated diene polymer (A) contained in the latex composition. By setting the amount of the vulcanization accelerator used within the above range, the tear strength of the obtained film molded article such as the dip molded article can be further increased.

[0118] Furthermore, the latex composition may further contain additives such as antioxidants, dispersants, activators, reinforcing agents such as carbon black, silica, and talc, fillers such as calcium carbonate and clay, ultraviolet absorbers, and plasticizers, as required.

[0119] The method for preparing the latex composition of the present invention is not particularly limited, and examples thereof include a method of mixing the latex of the water-insoluble conjugated diene polymer (A), the latex of the alkali-soluble conjugated diene polymer (B), and the sulfur-based vulcanizing agent and vulcanization accelerator, which are used as necessary, using a dispersing machine such as a ball mill, a kneader, or a disperser. In this case, the compounding agents such as the sulfur-based vulcanizing agent and the vulcanization accelerator may be mixed with the latex of the water-insoluble conjugated diene polymer (A) and the latex of the alkali-soluble conjugated diene polymer (B) after making them into an aqueous dispersion using the above-mentioned dispersing machine. In this case, when the pH of the latex composition is set to 6 or less, the alkali-soluble conjugated diene polymer (B), which constitutes the latex of the alkali-soluble conjugated diene polymer (B), is dispersed in water as a medium while maintaining the particulate state. On the other hand, when the pH of the latex composition is 8 or more, the alkali-soluble conjugated diene-based polymer (B) constituting the latex of the alkali-soluble conjugated diene-based polymer (B) dissolves or is hydrated in water as a medium, and the latex of the alkali-soluble conjugated diene-based polymer (B) exhibits the properties of an aqueous solution.

[0120] The solid content of the latex composition of the present invention is not particularly limited, but is preferably in the range of 15 to 50% by weight, more preferably 35 to 45% by weight, in order to improve control of the film thickness during dip molding.

[0121] In order to obtain a film-formed product such as a dip-molded product having sufficient mechanical strength, the latex composition of the present invention is preferably aged (also referred to as prevulcanization) before being subjected to film-forming such as dip-molding. Since the latex composition of the present invention contains the latex of the water-insoluble conjugated diene polymer (A) and the latex of the alkali-soluble conjugated diene polymer (B), a film-formed product such as a dip-molded product having high tear strength can be obtained even when the aging temperature is relatively low, preferably 15 to 35°C, more preferably 20 to 27°C, and the aging time is preferably 8 to 18 hours, more preferably 8 to 12 hours. From the viewpoint that a film molded product such as a dip molded product having high tear strength can be appropriately obtained even by maturing at a relatively low temperature for a short time, it is preferable to perform the maturing in a state where the pH of the latex composition is 8 or more, that is, in a state where the alkali-soluble conjugated diene-based polymer (B) constituting the latex of the alkali-soluble conjugated diene-based polymer (B) is dissolved or hydrated in water as a medium, and the latex of the alkali-soluble conjugated diene-based polymer (B) has properties of an aqueous solution.

[0122] <Dip-molded body> The dip-molded article of the present invention is a film-like molded article obtained by dip-molding the above-mentioned latex composition of the present invention. Dip molding is a method in which a mold is immersed in a latex composition, the composition is deposited on the surface of the mold, the mold is then removed from the composition, and the composition deposited on the surface of the mold is then dried. The mold before being immersed in the latex composition may be preheated. Furthermore, a coagulant may be used as necessary before the mold is immersed in the latex composition or after the mold is removed from the latex composition.

[0123] Specific examples of methods for using a coagulant include a method in which a mold before being immersed in the latex composition is immersed in a solution of the coagulant to adhere the coagulant to the mold (anodic coagulation immersion method) and a method in which a mold on which the latex composition has been deposited is immersed in a coagulant solution (Teague coagulation immersion method). Of these, the anodic coagulation immersion method is preferred in that it produces a dip-molded product with little thickness unevenness.

[0124] Specific examples of the coagulant include water-soluble polyvalent metal salts such as metal halides, such as barium chloride, calcium chloride, magnesium chloride, zinc chloride, and aluminum chloride; nitrates, such as barium nitrate, calcium nitrate, and zinc nitrate; acetates, such as barium acetate, calcium acetate, and zinc acetate; and sulfates, such as calcium sulfate, magnesium sulfate, and aluminum sulfate. Among these, calcium salts are preferred, and calcium nitrate is more preferred. These water-soluble polyvalent metal salts can be used alone or in combination of two or more.

[0125] The coagulant can usually be used as a solution of water, alcohol, or a mixture thereof, and is preferably used in the form of an aqueous solution. This aqueous solution may further contain a water-soluble organic solvent such as methanol or ethanol, or a nonionic surfactant. The concentration of the coagulant varies depending on the type of water-soluble polyvalent metal salt, but is preferably 5 to 50% by weight, more preferably 10 to 30% by weight.

[0126] After the mold is removed from the latex composition, the deposit formed on the mold is usually dried by heating under appropriately selected drying conditions.

[0127] Next, the dip-molded layer formed on the mold is crosslinked by heating. The crosslinking of the dip-molded layer can be carried out by carrying out a heat treatment at a temperature of 80 to 150°C, preferably for 10 to 130 minutes. The heating method can be an external heating method using infrared rays or heated air, or an internal heating method using high frequency waves. Of these, external heating using heated air is preferred. Before carrying out the heat treatment, the dip-molded layer may be immersed in water, preferably in warm water at 30 to 70°C, for about 1 to 60 minutes to remove water-soluble impurities (for example, excess emulsifier, coagulant, etc.). The operation of removing the water-soluble impurities may be carried out after the dip-molded layer is heat-treated, but it is preferable to carry out the operation before the heat treatment in order to more efficiently remove the water-soluble impurities.

[0128] The dip-molded layer is then removed from the dip-molding mold to obtain a dip-molded body. The method for removing the layer from the mold can be by peeling it off by hand or by using water pressure or compressed air. After the removal, the layer may be further heated at a temperature of 60 to 120°C for 10 to 120 minutes.

[0129] The film thickness of the dip-molded body is preferably 0.03 to 0.50 mm, more preferably 0.05 to 0.40 mm, and particularly preferably 0.08 to 0.30 mm.

[0130] The dip-molded article of the present invention is obtained by using the above-mentioned latex composition of the present invention, and therefore has high tear strength, and can be particularly suitably used as, for example, gloves. When the dip-molded article is a glove, in order to prevent adhesion at the contact surface between the dip-molded articles and to improve slipperiness when putting on and taking off the glove, inorganic fine particles such as talc or calcium carbonate or organic fine particles such as starch particles may be scattered on the glove surface, an elastomer layer containing fine particles may be formed on the glove surface, or the surface layer of the glove may be chlorinated.

[0131] In addition to the above-mentioned gloves, the dip-molded article of the present invention can also be used for medical supplies such as nipples for baby bottles, pipettes, tubes, water pillows, balloon sacs, catheters, condoms; toys such as balloons, dolls, balls; industrial supplies such as molds for pressure molding, gas storage bags; finger sacs, etc.

Examples

[0132] Hereinafter, the present invention will be described in detail with reference to examples, but the present invention is not limited to these examples. In the following, "parts" are based on weight unless otherwise specified. Various physical properties were measured as follows.

[0133] <Solid content concentration> Weigh 2 g of the sample accurately (weight: X2) into an aluminum dish (weight: X1), and dry it in a hot air dryer at 105 °C for 2 hours. Then, after cooling in a desiccator, measure the weight of the aluminum dish together (weight: X3), and calculate the solid content concentration according to the following formula. Solid content concentration (weight%) = (X3 - X1) × 100 / X2

[0134] <Volume average particle diameter> The volume average particle diameter of the polymer particles constituting the latex was measured using a laser diffraction particle size distribution measuring device (trade name "SALD2200", manufactured by Shimadzu Corporation).

[0135] <Absorbance at pH = 8> An aqueous potassium hydroxide solution as a pH adjuster was added to the latex to adjust it to pH = 8 and a solid content concentration of 3% by weight, and the absorbance at pH = 8 and 500 nm was measured with a spectrophotometer at a temperature of 25 °C.

[0136] <Amount of aggregates after aging at 25 °C for 24 hours> The latex composition was aged at 25°C for 24 hours, and the aged latex composition (solid content concentration: D% by weight, weight: E) was filtered using a 200 mesh stainless steel wire mesh (weight: C) whose weight had been measured in advance. This wire mesh was dried in a dryer at 105°C for 2 hours or more, and the weight of the wire mesh after drying (weight: F) was measured. Next, the amount of aggregates (weight%) in the latex composition was calculated according to the following formula. It can be determined that the smaller the amount of aggregates, the better the compounding stability. Amount of aggregates = [(FC) / (D x E)] x 10000 (weight%)

[0137] <Aging time to reach maximum strength> In this example, as described later, latex compositions after aging are obtained by changing the aging time, and dip-molded bodies are produced using the latex compositions after aging with different aging times. The tensile strength is measured by the following method to obtain the aging time required for the tensile strength to reach the maximum, which is defined as the aging time to reach the maximum strength. The tensile strength at this time is defined as the tensile strength at the time of reaching the maximum strength. It can be determined that the shorter the aging time to reach the maximum strength, the better the productivity. The specific method for measuring the tensile strength was as follows. First, the dip-molded body was punched out with a dumbbell (product name "Super Dumbbell (model: SDMK-100C)" manufactured by Dumbbell Co., Ltd.) based on ASTM D412 to prepare a test piece for measuring the tensile strength. The test piece was pulled at a pulling speed of 500 mm / min with a Tensilon universal testing machine (product name "RTG-1210" manufactured by Orientec Co., Ltd.) to measure the tensile strength (unit: MPa) immediately before breakage.

[0138] <Tear strength> Based on ASTM D624-00, the dip molded body was left in a constant temperature and humidity room at 23°C and 50% relative humidity for 24 hours or more, and then punched out with a dumbbell (product name "Die C", manufactured by Dumbbell Co., Ltd.) to prepare a test piece for measuring tear strength. The test piece was pulled at a tensile speed of 500 mm / min with a Tensilon universal testing machine (product name "RTG-1210", manufactured by A&D Co., Ltd.) to measure the tear strength (unit: N / mm). In this example, the tear strength at the aging time at which the maximum strength was reached (tear strength when the maximum strength was reached) and the tear strength after aging for 12 hours were measured. The higher the tear strength, the more excellent the mechanical strength of the dip-formed article.

[0139] <Synthesis Example 1> (Production of synthetic polyisoprene (A-1) latex) Synthetic polyisoprene (product name "NIPOL IR2200L", manufactured by Zeon Corporation) was mixed with n-hexane (boiling point: 69°C) and dissolved by heating to 60°C with stirring to prepare an n-hexane solution of synthetic polyisoprene (a) with a synthetic polyisoprene concentration of 15% by weight.

[0140] On the other hand, potassium rosinate was added to water and dissolved by raising the temperature to 60° C. to prepare an aqueous emulsifier solution (b) with a concentration of 1.5% by weight.

[0141] Next, the synthetic polyisoprene n-hexane solution (a) obtained above and the emulsifier aqueous solution (b) were mixed using a mixer (product name "Multiline Mixer MS26-MMR-5.5L", manufactured by Satake Chemical Machinery Co., Ltd.) so that the potassium rosinate in the emulsifier aqueous solution (b) was 10 parts per 100 parts of synthetic polyisoprene in the synthetic polyisoprene n-hexane solution (a), and then mixed and emulsified at a rotation speed of 6000 rpm using an emulsifier (product name "Cavitron CD1020", manufactured by Pacific Machinery Co., Ltd.) to obtain an emulsified dispersion (c). At this time, the total feed flow rate of the synthetic polyisoprene n-hexane solution (a) and the emulsifier aqueous solution (b) was 2,000 kg / hr, the temperature was 60°C, and the back pressure (gauge pressure) was 0.5 MPa.

[0142] Next, the obtained emulsion dispersion (c) was heated to 80°C under reduced pressure of -0.01 to -0.09 MPa (gauge pressure) to distill off n-hexane, and an aqueous dispersion of synthetic polyisoprene (d) was obtained. At this time, an antifoaming agent (product name "SM5515", manufactured by Dow Corning Toray Co., Ltd.) was continuously added while spraying so that the amount was 300 ppm by weight relative to the synthetic polyisoprene in the emulsion dispersion (c). When distilling off n-hexane, the emulsion dispersion (c) was adjusted to 70% by volume or less of the tank volume, and stirring was performed slowly at 60 rpm using a three-stage inclined paddle impeller as the stirring impeller.

[0143] After completion of distillation of n-hexane, the obtained aqueous dispersion of synthetic polyisoprene (d) was concentrated by centrifuging at 8,000 to 9,000 G using a continuous centrifuge (product name "SRG610", manufactured by Alfa Laval) to obtain a latex (pH = 10.0) of synthetic polyisoprene (A-1) having a solid content concentration of 60% by weight as a light liquid. The conditions of the centrifugation were as follows: the aqueous dispersion (d) before centrifugation had a solid content concentration of 8% by weight, the flow rate during continuous centrifugation was 1300 kg / hr, and the back pressure (gauge pressure) of the centrifuge was 0.1 MPa.

[0144] The volume average particle size and absorbance of the obtained latex of synthetic polyisoprene (A-1) were measured according to the above-mentioned methods, and the results are shown in Table 1.

[0145] <Synthesis Example 2> (Preparation of latex of synthetic polyisoprene grafted with methacrylic acid (B'-4)) The synthetic polyisoprene (A-1) latex obtained in the above Synthesis Example 1 was diluted with 130 parts of distilled water per 100 parts of synthetic polyisoprene. Then, 0.8 parts of sodium salt of β-naphthalenesulfonic acid formalin condensate (trade name "Demol T-45", manufactured by Kao Corporation) as a dispersant per 100 parts of synthetic polyisoprene (A-1) was diluted with 4 parts of distilled water per 100 parts of synthetic polyisoprene (A-1) and added to the latex of synthetic polyisoprene (A-1) over 5 minutes. Next, the synthetic polyisoprene (A-1) latex to which the dispersant was added was charged in a nitrogen-substituted reaction vessel equipped with a stirrer, and the temperature was heated to 30°C while stirring. In addition, a methacrylic acid dilution solution was prepared by mixing 5 parts of methacrylic acid as a carboxyl group-containing compound and 16 parts of distilled water in a separate vessel. This diluted methacrylic acid solution was added to a reaction vessel kept at a temperature of 20° C. over a period of 30 minutes.

[0146] Furthermore, a solution (e) consisting of 7 parts of distilled water, 0.32 parts of sodium formaldehyde sulfoxylate (trade name "SFS", manufactured by Mitsubishi Gas Chemical Co., Ltd.), and 0.01 parts of ferrous sulfate (trade name "Frost Fe", manufactured by Chubu Chelest Co., Ltd.) was prepared using another container. After transferring this solution (e) into a reaction container, 0.5 parts of 1,1,3,3-tetramethylbutyl hydroperoxide (trade name "Perocta H", manufactured by Nippon Oil & Fats Co., Ltd.) was added and reacted at 20°C for 1 hour, and then a 5 wt% aqueous potassium hydroxide solution was further added to adjust the pH to 8.2, and then concentrated by a centrifuge to obtain a latex (pH = 8.1) of a synthetic polyisoprene methacrylic acid graft polymer (B'-4) with a solid content concentration of 57.0 wt%. The modification rate (graft rate) of the resulting latex of the synthetic polyisoprene methacrylic acid graft polymer (B'-4) was measured and found to be 0.3% by weight.

[0147] Furthermore, the volume average particle size and absorbance of the resulting latex of the methacrylic acid graft polymer of synthetic polyisoprene (B'-4) were measured according to the above-mentioned methods, and the results are shown in Table 1.

[0148] <Synthesis Example 3> (Preparation of latex of isoprene / methacrylic acid copolymer (B-1)) In a reaction vessel having an internal volume of 1 liter, 3 parts of sodium dodecylbenzenesulfonate and 180 parts of water were charged, and 58 parts of methacrylic acid and 0.60 parts of t-dodecyl mercaptan were added thereto. Then, the gas inside was replaced with nitrogen three times, and the reaction vessel was kept at 5°C, and 42 parts of isoprene, 0.005 parts of an activator (EDTA iron Na complex), 0.064 parts of sodium formaldehyde sulfoxylate (trade name "SFS", manufactured by Mitsubishi Gas Chemical Co., Ltd.), and 0.09 parts of 1,1,3,3-tetramethylbutyl hydroperoxide (trade name "Perocta H", manufactured by Nippon Oil & Fats Co., Ltd.) were charged, and a polymerization reaction was carried out for 20 hours. Then, an aqueous potassium hydroxide solution was added, and a latex of isoprene / methacrylic acid copolymer (B-1) with a solid content concentration of 3% by weight and a pH of 8 was obtained. The volume average particle size and absorbance of the latex of isoprene / methacrylic acid copolymer (B-1) were measured according to the above-mentioned method, and the results are shown in Table 1. The amount of each monomer unit in the obtained isoprene / methacrylic acid copolymer (B-1) was almost the same as the amount charged, and the weight average molecular weight (Mw) was 260,000 (a value calculated in terms of standard polystyrene by gel permeation chromatography analysis, the same applies to Synthesis Examples 4 and 5 below).

[0149] <Synthesis Example 4> (Preparation of latex of isoprene / methacrylic acid copolymer (B-2)) A latex of isoprene / methacrylic acid copolymer (B-2) having a solid content concentration of 3% by weight and pH=8 was obtained in the same manner as in Synthesis Example 3, except that the amount of methacrylic acid used was 25 parts and the amount of isoprene used was 75 parts. The volume average particle size and absorbance of the latex of isoprene / methacrylic acid copolymer (B-2) were measured according to the above-mentioned methods, and the results are shown in Table 1. The amount of each monomer unit in the obtained isoprene / methacrylic acid copolymer (B-2) was almost the same as the amount charged, and the weight average molecular weight (Mw) was 240,000.

[0150] <Synthesis Example 5> (Preparation of latex of isoprene / methacrylic acid copolymer (B-3)) A latex of isoprene / methacrylic acid copolymer (B-3) having a solid content concentration of 26% by weight and a pH of 8 was obtained in the same manner as in Synthesis Example 3, except that the amount of methacrylic acid used was 10 parts and the amount of isoprene used was 90 parts. The volume average particle size and absorbance of the latex of isoprene / methacrylic acid copolymer (B-3) were measured according to the above-mentioned methods, and the results are shown in Table 1. The amount of each monomer unit in the obtained isoprene / methacrylic acid copolymer (B-3) was almost the same as the amount charged, and the weight average molecular weight (Mw) was 320,000.

[0151] <Example 1> (Preparation of Latex Composition) To the latex of synthetic polyisoprene (A-1) obtained in Synthesis Example 1, the latex of isoprene / methacrylic acid copolymer (B-1) obtained in Synthesis Example 3 was added so that the amount of the latex of isoprene / methacrylic acid copolymer (B-1) was 0.8 parts per 100 parts of synthetic polyisoprene (A-1) in the latex of synthetic polyisoprene (A-1). Then, while stirring the obtained mixture, 1.5 parts of zinc oxide, 1.5 parts of sulfur, 2 parts of an antioxidant (product name "Wingstay L", manufactured by Chukyo Yushi Co., Ltd.), and 2 parts of zinc diisopropylxanthate (crosslinking accelerator) were added in terms of solid content relative to 100 parts of synthetic polyisoprene (A-1) in the mixture, and an appropriate amount of an aqueous potassium hydroxide solution as a pH adjuster was added to obtain a latex composition with a pH of 10.1.

[0152] (Aging of latex composition) The obtained latex composition was then placed in a thermostatic bath at 25° C. for aging. In this example, in order to determine the aging time to reach the maximum strength by measuring the relationship between the aging time and the time at which the tensile strength reaches the maximum, samples were taken every 2 hours after the start of aging to obtain latex compositions after aging with different aging times, and each of them was subjected to the following dip molding.

[0153] (Production of dip-molded body) A commercially available ceramic hand mold (manufactured by Shinko Co., Ltd.) was washed and preheated in an oven at 70°C, then immersed in an aqueous coagulant solution containing 18% by weight of calcium nitrate and 0.05% by weight of polyoxyethylene lauryl ether (trade name "Emulgen 109P", manufactured by Kao Co., Ltd.) for 5 seconds and removed from the aqueous coagulant solution. The hand mold was then dried in an oven at 70°C for 30 minutes or more to allow the coagulant to adhere to the hand mold, thereby coating the hand mold with the coagulant. The hand mold covered with the coagulant was then removed from the oven and immersed in the latex composition after aging (latex composition after aging with different aging times) obtained above for 10 seconds. The hand mold was then air-dried at room temperature for 10 minutes, and then immersed in 60°C warm water for 5 minutes to dissolve water-soluble impurities, forming a dip-molded layer on the hand mold. The dip-molded layer formed on the hand mold was then vulcanized by heating in an oven at a temperature of 120°C for 30 minutes, cooled to room temperature, and talc was sprayed on it before peeling it off from the hand mold to obtain a glove-shaped dip-molded product. The tensile strength of the obtained dip-molded product was then measured according to the above method to measure the aging time until the maximum strength was reached, and the tensile strength at the time of reaching the maximum strength, the tear strength at the time of reaching the maximum strength, and the tear strength after 12 hours were measured. The results are shown in Table 1.

[0154] <Example 2, Comparative Examples 1 to 4> The latex compositions were prepared, aged, and dip-molded in the same manner as in Example 1, and evaluated in the same manner, except that the latexes obtained in Synthesis Examples 1 to 5 were used in the amounts shown in Table 1 (the amounts calculated as the polymers (solid content) contained in each latex) and the pH of the latex compositions was set to those shown in Table 1. The results are shown in Table 1. In addition, in Comparative Example 4, it was not possible to form a dip-molded layer by dip molding.

[0155] [Table 1]

[0156] As shown in Table 1, the latex composition containing the latex of the water-insoluble conjugated diene polymer (A) having an absorbance of 0.3 or more at pH=8 and a solid content concentration of 3% by weight, and the latex of the alkali-soluble conjugated diene polymer (B) having an absorbance of less than 0.3 at pH=8 and a solid content concentration of 3% by weight, which is obtained by emulsion polymerization of a monomer mixture containing a conjugated diene monomer and a water-soluble monomer, has a short maturation time to reach maximum strength, and therefore can exhibit sufficient strength even when maturated at a relatively low temperature and for a short maturation time, and the obtained dip-molded article has high tear strength (Examples 1 and 2). On the other hand, when the latex of the water-insoluble conjugated diene polymer (A) was not contained, or when the latex of the alkali-soluble conjugated diene polymer (B) was not contained, the maturation time to reach maximum strength was long, resulting in poor productivity (Comparative Examples 1 to 3), the tear strength of the obtained dip-molded body was low (Comparative Example 3), or a dip-molded layer could not be formed (Comparative Example 4).

Claims

1. a latex of a water-insoluble conjugated diene polymer (A) having an absorbance of 1.0 or more at pH 8 and a solid content of 3% by weight; and a latex of an alkali-soluble conjugated diene polymer (B) having an absorbance of less than 0.3 at pH=8 and a solid content concentration of 3% by weight, The absorbance is measured by adding an aqueous potassium hydroxide solution to the latex to adjust the pH to 8 and the solid content to 3% by weight, and using a spectrophotometer at a temperature of 25° C. and a wavelength of 500 nm. the content of the alkali-soluble conjugated diene polymer (B) contained in the latex of the alkali-soluble conjugated diene polymer (B) is 0.01 to 2 parts by weight based on 100 parts by weight of the water-insoluble conjugated diene polymer (A) contained in the latex of the water-insoluble conjugated diene polymer (A); the latex of the water-insoluble conjugated diene-based polymer (A) is a synthetic polyisoprene latex or a deproteinized natural rubber latex, The latex of the alkali-soluble conjugated diene polymer (B) is a latex composition obtained by emulsion polymerization of a monomer mixture containing a conjugated diene monomer and a water-soluble monomer.

2. The latex composition according to claim 1, wherein the volume average particle diameter of particles of the alkali-soluble conjugated diene polymer (B) in the latex of the alkali-soluble conjugated diene polymer (B) at pH = 6 or less is 60 to 200 nm.

3. 3. The latex composition according to claim 1, wherein the content of the water-soluble monomer unit in the alkali-soluble conjugated diene polymer (B) is 20 to 80% by weight based on 100% by weight of all monomer units.

4. The latex composition according to any one of claims 1 to 3, wherein the alkali-soluble conjugated diene polymer (B) is obtained by emulsion polymerization of a monomer mixture containing isoprene and a carboxyl group-containing monomer.

5. 5. The latex composition according to claim 4, wherein the carboxyl group-containing monomer is methacrylic acid.

6. A dip-molded article obtained by dip molding the latex composition according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Production of high-performance polyisoprene water latex, its gloves and related products

    CN101029163A

  • JP1975067855A

  • Aqueous polymer dispersion* paper coating composition and coated paper product made therewith

    JP1980145746A

  • Coating liquid composition for gravure printing paper

    JP1984045370A

  • Latex for coating paper

    JP1986055289A